Association between initial serum cystatin C level and prognosis of aneurysmal subarachnoid hemorrhage - Ruoran Wang; Jing Zhang; Jianguo Xu; Min He (BMC Neurology)
Abstract Background Aneurysmal subarachnoid hemorrhage (aSAH) patients usually suffer poor survival outcome and severe morbidity. Evaluating prognosis of aSAH patients in acute phase is essential for physicians to make suitable treatments strategies. This study was performed to explore the relation between initial serum cystatin C level and outcome of aSAH patients. Methods Three hundred seven aSAH patients were included. Univariate and multivariate logistic regression were used to analyze the relationship between initial serum cystatin C level with mortality and unfavorable functional outcome of aSAH patients. Receiver operating characteristic curve (ROC) was drawn and area under the ROC curve (AUC) was calculated to evaluate the prognostic value of serum cystatin C in aSAH. Results The incidence of mortality and unfavorable functional outcome in included 307 aSAH patients was 18.2% and 49.2%. Compared with survivors or patients with mRS < 3, non-survivors or those with mRS ≥ 3 had lower GCS and higher WFNS, Hunt-Hess, mFisher score. Serum cystatin C level was also higher in non-survivors or whose mRS ≥ than survivors or whose mRS < 3. Multivariate logistic regression showed serum cystatin C was significantly associated with mortality (p = 0.012) but not unfavorable functional outcome (p = 0.053) of aSAH. The AUC of serum cystatin C for predicting mortality and unfavorable functional outcome of aSAH patients was 0.718 and 0.669, respectively. Conclusions Initial serum cystatin C level is positively associated with mortality of aSAH patients. Evaluating serum cystatin C level is useful for clinicians to risk the severity of aSAH patients and therefore make personalized treatments regimen.